Original paperThe impact of activating source dwell positions outside the CTV on the dose to treated normal tissue volumes in TRUS guided 3D conformal interstitial HDR brachytherapy of prostate cancer - Karlsson, Leif; Thunberg, Per; Johansson, Bengt; Persliden, Jan (Journal of Contemporary Brachytherapy, 2014)
Purpose : Dose coverage is crucial for successful treatment in mono-brachytherapy. Since few and very high dose fractions are used, there is an important balance between dwell positioning outside the clinical target volume (CTV) and possible damage on adjacent normal tissue. The purpose of this study was to evaluate the possibility of having dwell positions close to the CTV surface, while maintaining an acceptable dose distribution, and to investigate the robustness in terms of known geometrical uncertainties of the implant. Material and methods : This study included 37 patients who had received brachytherapy for prostate cancer as a monotherapy with the following schedules: 2 × 14 Gy or 3 × 11 Gy, each fraction separated by two weeks. The source dwell positions were activated 5 mm outside CTV. New optimizations were simulated for dwell positions at 3, 2, 1, and 0 mm. Inverse and graphical optimization were applied according to the relative dose constraints: V 100 CTV ≥ 97%, D max, urethra ≤ 110%, and D 10 rectal mucosa ≤ 65%. The V 100, normal tissue outside CTV was used to evaluate dose variations caused by different dwell positions. Prostate geometries and dose distributions for the different dwell positions outside the CTV were used to investigate the impact on the CTV dose distribution due to geometrical uncertainties. Results : Both V100, CTV, and V 100, normal tissue decreased, 98.6% to 92.2%, and 17 cm 3 to 9.0 cm 3 , for dwell activation from 5 mm to 0 mm. The evaluation of both simulated longitudinal geometrical uncertainties and different source dwell activations implied that V100, CTV ranged from 98.6% to 86.3%. Conclusions: It is possible to reduce the V 100, normal tissue by decreasing the source dwell positions outside the CTV from 5 to 3 mm, while maintaining dose constraints. In combination with the estimated geometrical uncertainties, however, the source dwell positions need to be 5 mm from the surface in order to maintain a robust implant.